(untitled) (Conference Zone, 2022)
Alcoholic liver disease ( NALHD ) is a chronic disease that occurs in people who do not consume more than the norm of alcohol, i.e. ethanol consumption does not exceed 40 g per day for men and 20 g for women, due to the accumulation of lipids in liver cells, morphologically steatosis, combines clinical and morphological changes manifested in the form of steatohepatitis , fibrosis, cirrhosis [ 1,2,3,6 ].